Wita, Wantri Kasma PENGARUH SUHU DAN KECEPATAN MOTOR MESIN PULTRUSION TERHADAP DIAMETER FILAMEN 3D PRINTING - Kasma Wita, Wantri; Irawan Malik; Sairul Effendi (Politeknik Negeri Sriwijaya, Indonesia, 2024)
3D printing technology enables the creation of 3D objects from 3D CAD designs using various types of thermoplastic materials, such as PLA, ABS, PET/-G, TPU, PP, and Nylon. Among these materials, PET stands out as an ideal choice for 3D printing applications due to its advantages, namely clarity and strength. The process of producing 3D objects involves the use of filaments that can be generated through either extrusion or pultrusion methods. While the pultrusion method with Arduino Uno control settings shows promise, further research is required to enhance the quality of the produced filaments. In this study, the filament production process involves process parameters, including temperatures of 140°C, 145°C, 150°C, and motor speeds of 75 rpm, 80 rpm, 85 rpm, and 90 rpm. Based on the research findings, the smallest filament diameter was observed at a temperature of 150°C and a motor speed of 90 rpm. Conversely, the largest filament diameter was found at a temperature of 140°C and a motor speed of 75 rpm with a nozzle diameter of 1.75 mm. The highest filament quality was achieved using a nozzle diameter of 1.6 mm, resulting in an average filament diameter of 1.75 mm. Through non-linear regression analysis, it can be concluded that each process parameter has a simultaneous impact on the filament diameter. The results of this study provide insights into optimizing process parameters in the pultrusion method to produce high-quality filaments in 3D printing technology.